Comparison of Atherosclerotic Calcification in Major Vessel Beds on the Risk of All-Cause and Cause-Specific Mortality: The Rotterdam Study. (December 2015) - Bos, Daniel; Leening, Maarten J.G.; Kavousi, Maryam; Hofman, Albert; Franco, Oscar H.; Lugt, Aad van der; Vernooij, Meike W.; Ikram, M. Arfan
Abstract : Background—: Atherosclerosis is a major contributor to global morbidity and mortality. Although atherosclerosis is a systemic disease, its burden varies considerably across vessel beds, which may translate into differences in mortality risk. Methods and Results—: From 2003 to 2006, a sample of 2408 elderly participants (mean age, 69.6±6.7 years; 52.4% female) from the population-based Rotterdam Study underwent computed tomography to quantify atherosclerotic calcification in the coronary arteries, aortic arch, extracranial, and intracranial internal carotid arteries. Mortality follow-up was complete until January 1, 2012. We investigated associations of calcification in each vessel bed with mortality using Cox regression, adjusting for age, sex, and cardiovascular risk factors. Next, all vessel beds were included into 1 model to investigate independency of associations. Finally, we investigated the predictive value of calcification beyond the predictors included in the Pooled Cohort equations. During 15 775 person-years of follow-up, 283 participants died. Larger calcification volumes in all vessels were related to higher risks of all-cause mortality, cardiovascular, and noncardiovascular mortality, independent of cardiovascular risk factors. Most prominent associations were found for aortic arch calcification and cardiovascular mortality (age- and sex-adjusted hazard ratio per 1-SD increase 2.72 [95% confidence interval, 1.85–4.02]), independent of calcification elsewhere (hazard ratio, 1.75 (95% confidence interval, 1.13–2.72]). Calcification in any vessel improved prediction for all 3 outcomes. Conclusions—: Atherosclerotic load in major vessel beds is associated with an increased risk of death. In particular, aortic arch calcification volume yields unique information with regard to mortality in addition to atherosclerosis in other vessel beds. Abstract : Supplemental Digital Content is available in the text.